Pengukuran Dan Sosialisasi Terkait Pengetahuan Masyarakat Dalam Penanganan Infeksi Awal Influenza Melalui Media Sosial - Windhu Wardhana, Yoga; Ghozali, Dolih; Kautsar, Angga P.; Kurniawansyah, Insan Sunan (Yayasan Literasi Sains Indonesia, 2022)
Recently, the world has been hit by a pandemic caused by a virus of the type of influenza that spreads very quickly, called COVID-19. It is named that cause of the disease from this type of influenza virus is relatively new and has not been widely known and began to spread at the end of 2019. Influenza itself is an acute respiratory tract infection (ARTI) caused by an influenza virus from the Orthomyxoviridae family, which can cause mild to severe symptoms. To avoid the occurrence of more severe or recurrent infections requires prevention and proper handling of the influenza disease. But in fact, there are still many Indonesian people who underestimate this and think that the flu is an ordinary disease because this disease actually can heal on its own. To reduce the spread or break the chain of transmission of the influenza virus, the community needs to adequate awareness and knowledge given. Through virtual KKN-PPMD activities, we want to learn the extent of public knowledge about how to prevent and treat early influenza infection. In this activity, an assessment will be given at the beginning and end of providing education related to knowledge for the prevention and handling of early influenza infections. The provision of virtual education was distributed through social media (Youtube, Whatsapp, Instagram, Facebook). The activity results from the category of random respondents in which the majority were women by 73%, with ages ranging from 15-35 years and status as students, it was found that a significant increase in knowledge showed that from each groups as like age group, education level, and type of work, namely 3,495 (sig. 0.062), 5.017 (sig. 0.025), and 1.140 (sig. 0.286).